Hermeneutic Phenomenology In Qualitative Research - Mohammad Taghi Karami; Hamed Alizadeh (روش شناسی علوم انسانی, 2022)
Various methodologies have been proposed for phenomenology as a qualitative research method. This diversity can be divided into two main approaches: descriptive phenomenology and hermeneutic phenomenology. In this article, while emphasizing the inseparable link between philosophy and method in phenomenology, an attempt is made to explore the philosophical foundations of hermeneutic phenomenology and to trace this link in the research process. Accordingly, we first refer to the historical contexts of the emergence of phenomenology, and clarify the relationship between hermeneutic phenomenology and descriptive phenomenology, then Through the discussion of the views of Heidegger and Gadamer, it is shown that philosophical foundations in the method of hermeneutic phenomenology play an active role throughout the research process and give structure and direction to how we deal with issues and problems in research. Openness to the phenomenon and being in constant dialogue with it, is the most important feature of this method that as a praxis, from the moment of choosing the subject and encountering the research literature and theories to collecting and analyzing data and writing the research, it is always present and guides in the research